Can quiet standing posture predict compensatory postural adjustment? - Gabriel Bueno Lahóz Moya; Cássio Marinho Siqueira; Renê Rogieri Caffaro; Carolina Fu; Clarice Tanaka (Clinics, 2009)
OBJECTIVE: The aim of this study was to analyze whether quiet standing posture is related to compensatory postural adjustment. INTRODUCTION: The latest data in clinical practice suggests that static posture may play a significant role in musculoskeletal function, even in dynamic activities. However, no evidence exists regarding whether static posture during quiet standing is related to postural adjustment. METHODS: Twenty healthy participants standing on a movable surface underwent unexpected, standardized backward and forward postural perturbations while kinematic data were acquired; ankle, knee, pelvis and trunk positions were then calculated. An initial and a final video frame representing quiet standing posture and the end of the postural perturbation were selected in such a way that postural adjustments had occurred between these frames. The positions of the body segments were calculated in these initial and final frames, together with the displacement of body segments during postural adjustments between the initial and final frames. The relationship between the positions of body segments in the initial and final frames and their displacements over this time period was analyzed using multiple regressions with a significance level of p < 0.05. RESULTS: We failed to identify a relationship between the position of the body segments in the initial and final frames and the associated displacement of the body segments. DISCUSSION: The motion pattern during compensatory postural adjustment is not related to quiet standing posture or to the final posture of compensatory postural adjustment. This fact should be considered when treating balance disturbances and musculoskeletal abnormalities. CONCLUSION: Static posture cannot predict how body segments will behave during compensatory postural adjustment.